Selectivity and Internal Migration: A Study of Refugees' Dispersal Policy in Sweden - Haberfeld, Yitchak; Birgier, Debora Pricila; Lundh, Christer; Elldér, Erik (Frontiers in Sociology, 2019)
Following the intensified waves of refugees entering Europe, dispersal policies for newly arrived refugees have been proposed to speed up their integration and to share the financial burden across and within the EU countries. The effectiveness of dispersal policies depends, among other factors, on the extent to which refugees tend to stay in the initial location they are assigned to live in, and on their patterns of self-selectivity during subsequent moves of internal migration. Economic theories of migration suggest that economic immigrants are self-selected to destinations based on their abilities. Highly skilled and motivated people tend to migrate to labor markets with broader opportunity structures, while less capable individuals choose markets that are more sheltered. We use a quasi-experimental design to examine the extent to which those theories are first, applicable to refugees as well, and second, explain their self-sorting into local labor markets at destination. We focus on a refugee cohort that came to Sweden during the period when the so-called “Whole-Sweden” policy was in effect. This policy was designed to reduce the concentration of refugees in the larger cities by randomly deploying asylum seekers across Sweden. After being assigned to an initial location, refugees could move freely within Sweden. We use individual register data from Statistics Sweden to study all refugees who arrived in Sweden during 1990–1993, and we follow each one of them during an 8-year period. We use discrete-time survival analysis (complementary log-log models) in order to assess the effects of abilities on the destination choices of refugees, and individual fixed-effect models to assess the effects of internal migration on their income. Destinations were defined on the basis of the economic opportunities they offer. The results suggest that refugees' education levels are related to major differences in their destination choices. Highly skilled refugees were more likely to migrate to labor markets with a wide structure of opportunities relative to less skilled refugees. In addition, all relocation choices had positive effects on refugees' income growth.